REPRESENTASI FANATISME REMAJA TERHADAP KOREAN WAVE PADA IKLAN MC DONALD’S INDONESIA - Hakim, Lukman; Al Faricha, Rima Auliya (Universitas Teuku Umar, 2023)
The phenomenon of Korean culture has gone global. From this phenomenon, the term korean wave was born. Korean wave can have an impact on society, especially on teenagers. In addition to K-dramas, music and advertisements that highlight elements of Korean culture can also have an impact on society. Ads with the concept of Korean culture can attract audience attention than other advertising concepts. As in the MC Donald's Indonesia advertisement which introduces their new menu in the form of fried chicken with Korean special sauce. MC Donalds Indonesia Korean Soy Garlic wings advertisement illustrates some fanaticism behaviors in teenagers towards korean wave. This study finds out the MC DOnalds Indonesia advertisement in presenting teenage fanaticism towards korean wave through the selection of signs in the form of images in the advertisement. This research discusses how the attitude of a teenager who is identified as having a fanaticism attitude towards korean wave in MC Donald's Indonesia advertisements. This discussion aims to find out the image of a teenager who reflects fanaticism towards korean wave. The approach used in this research uses a descriptive qualitative approach by using the Charles S. Pierce semiotic analysis research method known as the triangle of meaning theory to analyze a sign. The results obtained that there are eight scenes of korean wave fanaticism in teenagers.